Determinants of market outlet choices by smallholder teff farmers in Dera district, South Gondar Zone, Amhara National Regional State, Ethiopia: A multivariate probit approach - Tadie Mirie Abate; Taye Melese Mekie; Abebe Birara Dessie (Journal of Economic Structures, 2019)
In Ethiopia, teff is an important cereal crop, particularly in Dera district. It is a source of food and provides cash income for majority of smallholder farmers. To commercialize teff producers, selecting an appropriate market channel is mandatory. However, selecting an appropriate market channel is not an easy task because there are different factors that influence market outlet choices. Therefore, this study aimed to identify factors that influence teff market outlet choices. A two-stage random sampling procedure was used and a total of 154 smallholder farmers were randomly and proportionally selected to collect primary data. Multivariate probit model was employed to identify factors affecting teff market outlet choices. The result of the study shows that the probability of teff producers to choose wholesaler, retailer, consumer and cooperative market outlets was 31.82%, 35.71%, 37.01% and 16.88%, respectively. This shows that consumer was the most likely chosen market outlet while cooperative was the less likely chosen market outlet. The joint probability of farmers to choose the four market outlets is (0.1%) lower than the likely of no choosing four market outlets (19.5%). The result of multivariate probit model revealed that age of household head, land size, quantity of teff produced, lagged price of teff, family size (AE), membership of cooperatives and distance to the nearest market were found to be statistically and significantly affecting the market outlet choice behavior of teff producers. This implies that improving the production capacity of farmers and invests on rural cooperatives would help smallholder farmers to choose the rewarding market outlet. Therefore, the study suggested that improving the existing production system, farmers relying on intensive cultivation; giving better price for farmers and being membership of cooperative are important strategies to select the appropriate market channel.
Keywords: 330; Tef; Market outlet choice; Multivariate probit